The effect of a counseling program on self-control and its impact on some offensive skills of fencing players under (20 years old) (Journal of the College of Basic Education, 2023)
Summary of the research:The field of physical education and sports sciences has witnessed in the recent period a great development and a remarkable interest in sports psychology and with regard to preparing psychological attitudes in a way that stimulates the player's motivations to reach sports achievement. As self-control represents the main part in preparing the player to acquire skills, attitudes, goals, and all dimensions of competition and everything related to it. The research problem has emerged with a lack of interest in the psychological aspect, in addition to the lack of psychological counseling programs for fencing players, the lack of use of the self-control program, and the knowledge of its effect on some offensive skills. The research aimed to prepare an indicative program according to the self-control of self-control and to know the extent of its impact on the offensive skills of the foil weapon. The experimental method was used with two experimental and control groups, as the research community reached (25) players, while the research sample amounted to (20) players from Diyala Club with fencing weapons. A number of conclusions were reached, including: - The self-control program had a positive effect on improving the performance of some offensive skills with fencing weapons for the experimental group. There are significant differences between the results of the experimental and control groups for some offensive skills of the foil weapon. The most important recommendations are: The need to conduct a study similar to this study on group games